Wassily Kandinsky: Seni Modern dan Teori - Hanny Wijaya (Bina Nusantara University, 2013)
Modern art development, especially in abstract art had been started since Expressionism period in Germany. Wassily Kandinsky was one of the pioneers of pure abstract art, he created his masterpieces not only as an artist, but also as an art theorist. Although at first he did not have the education background in art field, since Kandinskywas an academic faculty in art and economic, however he gained his success because of his high interest and spirit in art field.Besides, Kandinsky had created many art theories and perspectives of colors, compositions, forms, and had succeeded to apply it in his paintings. His style was inspired by Claude Monet’s painting ‘Haystack’ and the opera performance ‘Lohengrin’ by Richard Wagner. Kandinsky began to study new theories of art by learning art elements and principles more profound, he learned about colors deeply and tried to develop Goethe’s color theory, he also tried to elaborate the meaning of forms and applied the compositions in his artworks as well.